Learning Independence and Learning Achievement Mediated by Learning Motivation in E-learning-Based Lectures - Nashruddin Nashruddin; Musahrain Musahrain; Sitti Aisyah (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
The level of student learning independence in e-learning-based lectures has not been fully able to improve learning achievement without being supported by adequate learning motivation. This study aims to find the effect of the use of e-learning and learning independence, which is mediated by learning motivation, on learning achievement, in university level. This research is a quantitative study with a survey method, where learning motivation is a mediation variable or intervening, learning independence and the use of e-learning are independent variables, and learning achievement is the dependent variable. Involving 20 students of the English language education study program at Universitas Muslim Maros as research subjects, the researchers used documentation and distributing questionnaires to collect data. The data obtained were analyzed using path analysis using the application of IBM SPSS Statistics 19. This research finds that the use of e-learning has a significant effect on university students’ learning motivation, learning motivation has a significant effect on university students’ learning achievement; and can mediate the use of e-learning in influencing university students’ learning achievement. As an implementation in the development of science, the findings of this study reveal the fact that students’ learning outcomes are influenced by learning motivation, learning independence, and learning media such as e-learning.